2008
DOI: 10.1128/mcb.01298-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Internal Ribosome Entry Segment (IRES)-trans-Acting Factors for the Myc Family of IRESs

Abstract: The proto-oncogenes c-, L-, and N-myc can all be translated by the alternative method of internal ribosome entry whereby the ribosome is recruited to a complex structural element (an internal ribosome entry segment [IRES]). Ribosome recruitment is dependent upon the presence of IRES-trans-acting factors (ITAFs) that act as RNA chaperones and allow the mRNA to attain the correct conformation for the interaction of the 40S subunit. One of the major challenges for researchers in this area is to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 50 publications
6
111
1
Order By: Relevance
“…It has been shown that the 5 0 untranslated region of c-myc, which is encoded by exon 1, contains an IRES (Nanbru et al, 1997;Stoneley et al, 1998) that functions to maintain c-myc expression during a number of pathophysiological conditions including apoptosis , genotoxic stress (Subkhankulova et al, 2001) and viral infection (Johannes and Sarnow, 1998). c-myc IRESmediated translation requires both canonical initiation factors (Spriggs et al, 2009) and specific IRES-transacting factors (ITAFs) and these have been shown to include Y-box binding protein 1 (YB-1), PSF, P54nrb, GRSF1, polypyrimidine tract-binding protein 1 (PTB-1), hnRNPK and hnRNPA1 (Evans et al, 2003;Cobbold et al, 2008;Jo et al, 2008). It has been proposed that ITAFs stimulate IRES-mediated translation by acting as RNA chaperones and allowing the IRES to adopt the correct conformation so that the 40S ribosomal subunit can bind (Stoneley and Willis, 2004b).…”
mentioning
confidence: 99%
“…It has been shown that the 5 0 untranslated region of c-myc, which is encoded by exon 1, contains an IRES (Nanbru et al, 1997;Stoneley et al, 1998) that functions to maintain c-myc expression during a number of pathophysiological conditions including apoptosis , genotoxic stress (Subkhankulova et al, 2001) and viral infection (Johannes and Sarnow, 1998). c-myc IRESmediated translation requires both canonical initiation factors (Spriggs et al, 2009) and specific IRES-transacting factors (ITAFs) and these have been shown to include Y-box binding protein 1 (YB-1), PSF, P54nrb, GRSF1, polypyrimidine tract-binding protein 1 (PTB-1), hnRNPK and hnRNPA1 (Evans et al, 2003;Cobbold et al, 2008;Jo et al, 2008). It has been proposed that ITAFs stimulate IRES-mediated translation by acting as RNA chaperones and allowing the IRES to adopt the correct conformation so that the 40S ribosomal subunit can bind (Stoneley and Willis, 2004b).…”
mentioning
confidence: 99%
“…Most intermolecular nOes were derived from filtered-edited NOESY experiments using 15 N- 13 C labeled proteins and unlabeled RNA ( Supplementary Fig. 2a).…”
Section: Structure Determination Of the Qrrm-rna Complexesmentioning
confidence: 99%
“…We would like to thank D. Black for providing the clone of full-length hnRNP F and S. Pitsch for providing sugar- 13 …”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRES of XIAP has been linked to binding of La autoantigen, hnRNPC1/2 and DAP5 (7). A recent study using proteomic approaches found four proteins: G-rich RNA sequence binding factor 1 (GRSF-1), Y-box binding protein 1 (YB-1), PTB associated splicing factor (PSF), and its binding partner p54nrb, as ITAFs for regulating translation of myc family genes (10). In this study, we report the finding of La autoantigen as an ITAF regulating Nrf2 protein translation under oxidative stress.…”
mentioning
confidence: 99%